Communities in transformation: An archaeological survey from the 12th to the 9th century BC - Lemos, I (Peeters, 2014)
In this paper, I will explore the period after 1200 BC which marks the beginning of significant transformations that took place after the collapse of the Mycenaean administration system. In particular, I will focus on the earlier part of the period and trace the changes in settlement planning, burial rites and cult. Specific regions and sites will be discussed which highlight not only important breaks but also continuities from the Mycenaean past. Recent discoveries and debates will also be summarised, illustrating the significance of this period